A rare case of capillary hemangioma mimicking glomus tympanicum in a 38 years old male - Anand Singh, Huidrom; Agarwal, Vaishali; Madathumpady Abdussalam, Mishal Fathima; Patil, Amol Anandrao; Vora, Uday (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Capillary hemangiomas of the middle ear are rare benign vascular neoplasms characterized by abnormal proliferation of small blood vessels. We report a case of a 38-year-old male who presented with episodes of otorrhea, aural fullness, otalgia, and hearing loss in the left ear. Otoscopic examination revealed a thickened, reddish, non-pulsatile tympanic membrane. Pure tone audiometry demonstrated mild conductive hearing loss, and CT imaging of the temporal bone showed a soft tissue mass in the mesotympanum and epitympanum. Surgical exploration and histopathology confirmed the diagnosis of a capillary hemangioma. Surgical excision remains the mainstay of treatment, with histopathology as the definitive diagnostic tool. Long-term follow-up is recommended due to the risk of recurrence.